2022
DOI: 10.3389/fnins.2021.748080
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Phase-Encoding Direction on Gender Differences: A Resting-State Functional Magnetic Resonance Imaging Study

Abstract: AimNeuroimaging studies have highlighted gender differences in brain functions, but conclusions are not well established. Few studies paid attention to the influence of phase-encoding (PE) direction in echo-planar imaging on gender differences, which is a commonly used technique in functional magnetic resonance imaging (fMRI). A disadvantage of echo-planar images is the geometrical distortion and signal loss due to large susceptibility effects along the PE direction. The present research aimed to clarify how P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 63 publications
2
4
0
Order By: Relevance
“…Statistically, regions consistently influenced by PED in both atlases were primarily the cingulate cortex, temporal cortex, sensorimotor area, and visual area. This is similar to results in previous studies that both functional connectivity strength and amplitude of low-frequency fluctuation (ALFF) in these regions are strongly affected by PED ( Mori et al, 2018 ; Wang et al, 2021 ). Notably, these regions are not only along the PE axis during imaging acquisition but also close to air/tissue interface, which possibly suffer magnetic susceptibility induced image distortion and propagated flow or motion artifacts ( De Panfilis and Schwarzbauer, 2005 ; Weiskopf et al, 2006 ).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Statistically, regions consistently influenced by PED in both atlases were primarily the cingulate cortex, temporal cortex, sensorimotor area, and visual area. This is similar to results in previous studies that both functional connectivity strength and amplitude of low-frequency fluctuation (ALFF) in these regions are strongly affected by PED ( Mori et al, 2018 ; Wang et al, 2021 ). Notably, these regions are not only along the PE axis during imaging acquisition but also close to air/tissue interface, which possibly suffer magnetic susceptibility induced image distortion and propagated flow or motion artifacts ( De Panfilis and Schwarzbauer, 2005 ; Weiskopf et al, 2006 ).…”
Section: Discussionsupporting
confidence: 92%
“…This raises concern as whether PED would have significant effects on test-retest reliability of the derived connectomic measures. Notably, recent studies have demonstrated significant PED-related effects on the connectivity outcome in comparison of patients with schizophrenia and healthy controls ( Mori et al, 2018 ) as well as contrasting males and females ( Wang et al, 2021 ), further strengthening the possibility of such concern.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…Statistically, regions that were consistently influenced by PED in both atlases were the ACC and temporal cortex. This is remarkably similar to results in previous studies that both functional connectivity strength and amplitude of low-frequency fluctuation (ALFF) in these regions are strongly affected by PED (Mori et al, 2018; Wang et al, 2021). Notably, these regions are not only along the PE axis during imaging acquisition but also close to air/tissue interface, which possibly suffer magnetic susceptibility induced image distortion and propagated flow or motion artifacts (De Panfilis and Schwarzbauer, 2005; Weiskopf et al, 2006).…”
Section: Discussionsupporting
confidence: 92%